OCT Angiography-Derived Retinal Capillary Perfusion Measures in the Framingham Heart Study - Ana D. Collazo Martinez, BS; Shu Jie Ting, MA; Anoush Shahidzadeh, MPH; Brinda Vaidya, BS; Tim Kowalczyk, MBA; Muhammed Alluwimi, PhD; Sujata Rijal, PhD; Xuejuan Jiang, PhD; Ruikang Wang, PhD; Alexa Beiser, PhD; Lucia Sobrin, MD, MPH; Sudha Seshadri, MD, DM; et al. (Ophthalmology Science)
Purpose: To report baseline demographic associations and novel intereye correlations of retinal perfusion in the Framingham Heart Study (FHS). Design: Cross-sectional study. Participants: One thousand eighteen participants were recruited. Of these, 962 participants (mean age 75 ± 7, 59% female, 1720 undilated eyes) had any OCT angiography (OCTA) data. Methods: Participants from the community-based FHS were recruited between 2020 and 2022. Foveal-centered 3 × 3 mm2 OCTA scans were used to noninvasively measure retinal capillary perfusion in both undilated eyes of each subject. Retinal capillary perfusion measures, including vessel skeleton density (VSD), vessel area density (VAD), and flux, were calculated in the superficial retinal layer, deep retinal layer (DRL), and full retinal thickness. Multivariate mixed-effect models were used to examine the association between retinal perfusion measures and eye laterality, sex, image quality, axial length (AL), and age. Correlation of retinal perfusion measures between 2 eyes of individual participants was assessed. Main Outcome Measures: Vessel skeleton density, VAD, and flux. Results: One thousand two hundred forty-four eyes (73%) had usable OCTA data with 52% acquired from the right eye. Although there was a significant correlation of retinal perfusion measures between 2 eyes of an individual, this was only moderate in magnitude (R = 0.6, P < 0.000). There was also a significant decrease in retinal perfusion with age (P < 0.001) after controlling for sex, image quality, eye laterality, and AL. A potential interaction between age and layer-specific retinal perfusion was found (P = 0.058). Similar findings were observed with all measures of retinal perfusion (VAD, VSD, and flux). Projection artifact removal accounted for 9% to 34% (P < 0.050) of the variation in capillary perfusion measures in the DRL. Conclusions: Retinal capillary perfusion measures between 2 eyes of an individual share only moderate correlation even after adjusting for image quality and scan level artifacts. This has important implications in study design and interpretation of data from unilaterally performed studies on the retinal circulation. These data suggest that intereye differences in retinal perfusion have physiological and disease-related causes that warrant further investigation. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.